Mechanism of Anti-bacterial Activity of Zinc Oxide Nanoparticle Against Carbapenem-Resistant Acinetobacter baumannii - Tiwari, Vishvanath; Mishra, Neha; Gadani, Keval; Solanki, P. S.; Shah, N. A.; Tiwari, Monalisa (Frontiers in Microbiology, 2018)
Acinetobacter baumannii is a multi-drug resistant opportunistic pathogen, which causes respiratory and urinary tract infections. Its prevalence increases gradually in the clinical setup. Carbapenems (beta-lactam) are most effective antibiotics till now against A. baumannii, but the development of resistance against it may lead to high mortality. Therefore, it is of utmost importance to develop an alternative drug against A. baumannii. In the present study, we have synthesized ZnO nanoparticle (ZnO-NPs) and characterized by X-ray diffraction, Fourier transform infrared (FTIR) spectroscopy and UV-Visible spectroscopy. Prepared ZnO-NPs have the size of 30nm and have different characteristics of ZnO nanoparticles. Growth kinetics and disc diffusion assay showed that ZnO nanoparticle demonstrated good antibacterial activity against carbapenem resistant A. baumannii. We have also investigated the mechanism of action of ZnO-NPs on the carbapenem resistant strain of A. baumannii. The proposed mechanism of action of ZnO involves the production of reactive oxygen species, which elevates membrane lipid peroxidation that causes membrane leakage of reducing sugars, DNA, proteins, and reduces cell viability. These results demonstrate that ZnO nanoparticle could be developed as alternative therapeutics against A. baumannii.